Islam and Local Interest in The Safar Bath Tradition of Malay People in Sungai Jambu Sub Village Kayong Utara - Nurhayati, Dewi (Khatulistiwa, 2018)
Malay people are known to have diverse traditions as ancestral cultural heritage. One of the Malay cultural heritages of Sungai Jambu sub vilage is the form of a Safar Bath Tradition which is believed to be an effort to avoid being bala. Safar baths that are held every Safar Month are followed by the Malay Community of Sungai Jambu Sub village, both men and women and elders and young people. This article explains that Islam and the elements of local wisdom play an important role in the Tradition of Safar Baths. In fact there has been a mixture of Islam and local wisdom in the Safar Bath Tradition. The community believes that the tradition can prevent or even eliminate all kinds of bad luck, disaster or future calamities. Likewise, if implemented it will avoid reinforcements and diseases.